2014
DOI: 10.1063/1.4862930
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromic undoped and Mg-doped VO2 thin films and nanoparticles: Optical properties and performance limits for energy efficient windows

Abstract: Undoped and Mg-doped thermochromic VO 2 films with atom ratios z ≡ Mg/(Mg + V) of 0 ≤ z < 0.21 were deposited by reactive DC magnetron sputtering onto heated glass and carbon substrates. Elemental compositions were found by Rutherford backscattering spectrometry. Optical constants were determined from transmittance and reflectance measurements and were used for modeling the optical properties of thin films and dilute nanoparticle composite layers below and above the critical temperature for thermochromic switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 79 publications
4
41
0
Order By: Relevance
“…It is likely that some or all of these oxide layers are able to impart oxidation protection of the underlying VO 2 . We also note that VO 2 -based nanoparticles may be of considerable interest for TC fenestration [11,[16][17][18]. Core-shell structures have been investigated recently with VO 2 cores surrounded by shells comprised of SiO 2 [44][45][46][47][48] or TiO 2 [49][50][51] and, again, the top layer may serve as oxidation protection.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…It is likely that some or all of these oxide layers are able to impart oxidation protection of the underlying VO 2 . We also note that VO 2 -based nanoparticles may be of considerable interest for TC fenestration [11,[16][17][18]. Core-shell structures have been investigated recently with VO 2 cores surrounded by shells comprised of SiO 2 [44][45][46][47][48] or TiO 2 [49][50][51] and, again, the top layer may serve as oxidation protection.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…It should be noted that such coatings may be desired not only for oxidation protection but for their optical functionality. Thus the top coating can provide anti-reflection and thereby enhance the luminous transmittance, which is advantageous for windows-related applications [11,16], and studies have been reported for anti-reflecting layers based on oxides of Si [32][33][34][35][36][37], Ti [36][37][38][39][40][41][42], Zr [43] and Al [37]. It is likely that some or all of these oxide layers are able to impart oxidation protection of the underlying VO 2 .…”
Section: Conclusion and Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Thin films and nanoparticle composites of VO 2 are of considerable interest for "smart" glazings in buildings as well as for numerous other technologies. 3,[12][13][14][15][16][17] Most optical applications of VO 2 require essentially non-scattering properties, and both films and nanoparticle composites have been subject to detailed studies recently. 13,15 Only a few prior investigations 9,[18][19][20][21][22][23][24][25] have considered light scattering, and we particularly note recent work by Jin et al 20,21 on diffuse transmittance through VO 2 -based functional fiber mats and by Moot et al 22 on composites of VO 2 and elastomers.…”
Section: Introductionmentioning
confidence: 99%